Competing for a cause - (:unkn) unknown (Hindustan Times, 2014)
The Universal Design Workshop, exhibition and several cultural programmes were held at School of Planning and Architecture, sports complex, MANIT campus, Bhopal from March 1 to 3 under National Student Design Competition. School of Planning and Architecture (SPA), Bhopal and Bhanuben Nanavati College of Architecture for Women (BNCA), Pune jointly won third prize.
Keywords: National Student Design Competition 2014; SPA Workshop; Universal Design Workshop; NSDC 2014; SPA Bhopal Achievments